"Shadowing" of the electromagnetic field of relativistic charged particles; Journal of Physics; Vol. 236, Iss. 1 - Naumenko G. A. Gennadiy Andreevich; Artru X.; Potylitsyn A. P. Alexander Petrovich; Popov Yu. A. Yuriy Anatolevich; Sukhikh L. G. Leonid Grigorievich; Shevelev M. V. Mihail Viktorovich (2010, 2010)
Title screen